2023
DOI: 10.13181/mji.cg.236928
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Comparison of ultrasonography and fluoroscopy as guides for extracorporeal shock wave lithotripsy in nephrolithiasis patients: a systematic review

Abstract: [This corrects the article DOI: 10.13181/mji.oa.226140]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…11 Furthermore, the operator's exposure to ionizing radiation should be taken into account. 12 Based on these results, we can only conclude that the US is not inferior to FS. Interestingly, however, Ordon et al demonstrated that a small but significant increase in FS time correlated with an increase in ESWL success rates.…”
Section: Discussionmentioning
confidence: 87%
“…11 Furthermore, the operator's exposure to ionizing radiation should be taken into account. 12 Based on these results, we can only conclude that the US is not inferior to FS. Interestingly, however, Ordon et al demonstrated that a small but significant increase in FS time correlated with an increase in ESWL success rates.…”
Section: Discussionmentioning
confidence: 87%